Pengembangan Material Berbasis Multimedia Untuk Peningkatan Efektifitas Pengajaran Konsep Dasar IPA Mahasiswa PGSD - Amran, Muhammad; Nurjannah, Nurjannah (Universitas Negeri Makassar, 2022)
The research aimed to know the activity and studenst’ response in Basic Science Concept lecture by using multimedia based material to the students of PGSD S1 Campus V Makassar Negeri University City Pare–Pare. Qualitative and descriptive statistic are used to analysed the data. The result shows that the average of exam 1 is 72,32 increase to 78,00 at exam 2. Observation Data towards teaching activity shows that 83,16% has fit to teaching scenario. Observation Data towards students’ activity shows the average score 85,71% good chategory. Students give positive response to all aspects with the range of 79 – 97%. As a conclusion, the use of interractive multimedia based material could improve teaching effectivity to Basic Science Concept lecture. Finally, it is recommended that lecturers should apply interractive multimedia based material in other subjects as a teaching model at PGSD S1 Makassar Negeri University City Pare – Pare Negeri